Shadow banking regulation - Tobias Adrian; Adam B. Ashcraft (Federal Reserve Bank of New York, 2012)
Shadow banks conduct credit intermediation without direct, explicit access to public sources of liquidity and credit guarantees. Shadow banks contributed to the credit boom in the early 2000s and collapsed during the financial crisis of 2007-09. We review the rapidly growing literature on shadow banking and provide a conceptual framework for its regulation. Since the financial crisis, regulatory reform efforts have aimed at strengthening the stability of the shadow banking system. We review the implications of these reform efforts for shadow funding sources including asset-backed commercial paper, triparty repurchase agreements, money market mutual funds, and securitization. Despite significant efforts by lawmakers, regulators, and accountants, we find that progress in achieving a more stable shadow banking system has been uneven.
Keywords: G28; G20; G24; G01; 330; shadow banking; financial regulation